Sodobne dileme prekrškovnega prava energetike (University of Maribor Press, 2020)
Contemporary Dilemmas of Minor Offences in Energy Legislation. Leading experts from the fields of energy law, scientists from the field of minor offences and misdemeanour law as well as some amongst of the most promising students at University of Maribor cooperated in the drafting process of this contribution. The result of this cooperation is the first monograph from the field of minor offences in energy law in Slovene language. It is one of the first monographs dedicated to this topic in general. The text was partly inspired by the final written report of the student project ENERJUST. The report was however heavily revisited. Multiple new chapters were drafted by academics and other experts and added after the conclusion of the student project. The monograph consists of twelve stand-alone chapters. Authors tackle diverse issues, focusing primarly on the open market aspects of the regulation. Topics such as nomotechnical and policy issues, ensuring adequate competition and consumer protection are addressed. With a view to sectorial legislation topics such as lex certa, blanket dispositions and ne bis in idem are furthermore addressed. Authors examine issues of supervisory procedures in the energy sector and conclude their contribution by connecting the field of minor offences to ethics and ethical codexes.